Legal Efforts to Protect Small Shareholders against the Negative Effects of Insider Trading Practices in TransactionsStocks in the Capital Market - Khomaini Khomaini (CV. Inara in Colaboration with www.stie-sampit.ac.id, 2025)
The Indonesian capital market as one of the strategic economic instruments plays an important role in collecting public funds to support national economic growth. However, in its development, insider trading practices are still a serious threat to market integrity, especially detrimental to minority shareholders who own less than five percent of the company's total shares. Insider trading practices occur when parties within the company utilize material information that has not been published to conduct stock transactions, thereby creating systematic information injustice. This study aims to analyze the vulnerability of minority shareholders to insider trading practices and examine the effectiveness of available legal protection mechanisms. The research method used is normative legal research with a statutory and conceptual approach, analyzing Law Number 8 of 1995 concerning the Capital Market, UUPT, and other related regulations. The results of the study indicate that minority shareholders face structural vulnerability due to limited access to information, imbalance of power in corporate decision-making, and minimal understanding of their rights. Insider trading practices harm them through direct financial losses, decreased trust in the market, and the creation of an unfair market. Available legal protection mechanisms include the BEI Auto Rejection system, civil lawsuits based on Article 111 of the Capital Market Law, the active role of the OJK in defending consumers, and various special rights of minority shareholders in the UUPT. This study concludes that effective protection requires an integrated approach that combines preventive and repressive protection, strengthening investor education, and the application of progressive legal principles that prioritize justice and the welfare of minority shareholders.